The 19th-century translations of the Napoleonic Code and the history of Polish legal terminology - Wismont, Magdalena; Woźniak, Ewa (Papers in Linguistics, 2020)
The article discusses the persistence of Polish legal terminology in the context of the legal changes that were introduced in the first half of the 19th c. after the Napoleonic Code had become public law in the Duchy of Warsaw. The presented research covers vocabulary related to three thematic fields: CARE, FAMILY and DIVORCE. The study compares the lexis that is associated with these areas and that can be found in the Napoleonic Code with the terms that had been used in Polish law until the end of the 18th century. The study, which focuses on the sameness of the terms rather than their referents, shows a large number of persistent legal terms: 44% of the terms used in the translations of the Napoleonic Code had been present in the Polish legal terminology earlier. It also indicates that the 19th-century translation of French law, which significantly differed from the legal tradition of the Commonwealth of Poland, was largely based on the already used terminology. Finally, the study shows that the translator used traditional synthetic terms when referring to basic legal concepts. The new terms, by contrast, include mostly multi-word equivalents of more complex legal concepts.